Safety review of hydroxyprogesterone caproate in women with a history of spontaneous preterm birth - Sibai, Baha (J Perinatol, 2020)
17-alpha-hydroxyprogesterone caproate (17P) has been in use for prevention of recurrent preterm birth since 2003 when the Meis trial was published. A requirement for Food and Drug Administration approval of 17P was a confirmatory trial, called “PROLONG”, which was recently completed, but did not replicate the efficacy demonstrated in the Meis trial. This review analyzes the safety data from each trial, as well as integrated data from the two trials. The relative risks (95% CI) with 17P versus placebo in the integrated dataset were 0.66 (0.25–1.78) for miscarriage, 1.83 (0.68–4.91) for stillbirth, and 0.86 (0.53–1.41) for all fetal and neonatal death. The rate of gestational diabetes in the integrated dataset was 3.6% for 17P vs. 3.8% for placebo. Similar findings with low and comparable rates between 17P and placebo were also found for other adverse events. The integrated safety data demonstrate a favorable safety profile that was comparable to placebo.